The termination of UHRF1-dependent PAF15 ubiquitin signaling is regulated by USP7 and ATAD5 - Ryota Miyashita; Atsuya Nishiyama; Weihua Qin; Yoshie Chiba; Satomi Kori; Norie Kato; Chieko Konishi; Soichiro Kumamoto; Hiroko Kozuka-Hata; Masaaki Oyama; Yoshitaka Kawasoe; Toshiki Tsurimoto; et al. (eLife, 2023)
UHRF1-dependent ubiquitin signaling plays an integral role in the regulation of maintenance DNA methylation. UHRF1 catalyzes transient dual mono-ubiquitylation of PAF15 (PAF15Ub2), which regulates the localization and activation of DNMT1 at DNA methylation sites during DNA replication. Although the initiation of UHRF1-mediated PAF15 ubiquitin signaling has been relatively well characterized, the mechanisms underlying its termination and how they are coordinated with the completion of maintenance DNA methylation have not yet been clarified. This study shows that deubiquitylation by USP7 and unloading by ATAD5 (ELG1 in yeast) are pivotal processes for the removal of PAF15 from chromatin. On replicating chromatin, USP7 specifically interacts with PAF15Ub2 in a complex with DNMT1. USP7 depletion or inhibition of the interaction between USP7 and PAF15 results in abnormal accumulation of PAF15Ub2 on chromatin. Furthermore, we also find that the non-ubiquitylated form of PAF15 (PAF15Ub0) is removed from chromatin in an ATAD5-dependent manner. PAF15Ub2 was retained at high levels on chromatin when the catalytic activity of DNMT1 was inhibited, suggesting that the completion of maintenance DNA methylation is essential for the termination of UHRF1-mediated ubiquitin signaling. This finding provides a molecular understanding of how the maintenance DNA methylation machinery is disassembled at the end of the S phase.